The Emergence of Fintech on Cost Management in Malaysian Financial Institutions - Nik Abdullah, Nik Herda; Wei Ling, Tye (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
A good cost management system is vital in ensuring that the final product or service costs do not reflect a large variance from budgeted financial targets. Over time, new information and technologies may be introduced that completely change the production method, business process, or product itself. The term